Polymer Surface Modification: Relevance to Adhesion, Volume 4
DOI: 10.1163/ej.9789067644532.i-306.10
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment And Surface Modification Of Polymers Via Atmospheric-Pressure Plasma Jet Treatment

Abstract: Fluoropolymers are difficult materials to modify the surfaces because of strong C-F bonds. In this study, the surface modification of fluoropolymer films such as polytetrafluoroethylene (PTFE) with amino groups was performed by using He/NH 3 gas mixture atmospheric pressure plasma jets with negatively-biased substrate. It is expected that the ion bombardment effect onto the polymer surface due to negative substrate bias will make dangling bonds over the polymer surface and eventually promote the surface modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Not only the chemical structure but also the roughness of the surface is affected by the plasma treatment, which also could change the wettability of the surface [18]. Plasma treatment usually strengthens the hydrophilicity of treated polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the chemical structure but also the roughness of the surface is affected by the plasma treatment, which also could change the wettability of the surface [18]. Plasma treatment usually strengthens the hydrophilicity of treated polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…O tratamento por plasma produz mudanças físico-químicas na superfície do polímero, as quais podem alterar a rugosidade que, por sua vez, pode mudar a molhabilidade da superfície [18,19]. Também, o plasma pode gerar grupos funcionais que deixam a superfície polimérica mais hidrofílica.…”
Section: Resultados E Discussõesunclassified
“…In a previous study 13 , we observed a considerable increase in the roughness of the single fiber surface after the APP treatment of PET fabrics. Such topographical changes can arise from thermal effects of the plasma or from chemical reactions and sputtering 25 . Figure 4 shows optical microscopic images of stearic acid deposited on the PET film.…”
Section: Resultsmentioning
confidence: 99%